In vitro and in vivo investigation into the role of lysine specific demethylases in the molecular circadian oscillator - Shepherd, H (2015)
Lysine Specific Demethylases (LSD1 and LSD2 also known as KDM1A and KDM1B) are histone modifiers known to specifically demethylate dimethyl and monomethyl H3K4. They play roles in development and cancer mechanisms through regulation of the cell cycle and progenitor differentiation pathways but have not yet been characterised in the circadian system. LSD1 and LSD2 were shown to play a role in circadian oscillation in vitro in unpublished preliminary work. Knockdown of either gene caused dampened circadian oscillations of gene and protein expression. However, circadian rhythms could not be assessed in vivo as the Kdm1a-/- animal was embryonic lethal and the Kdm1b-/- animal displayed reproductive deficits. In order to generate a viable animal model of LSD disruption for assessment of adult circadian phenotypes in vivo the Harwell ENU mutant archive was screened for ENU-induced point mutations in non-catalytic domains of the two genes. The mutations found in the screen were investigated in vitro and in silico, and subsequently four mutations chosen for re-derivation by IVF (Kdm1aE440G, Kdm1aL491H, Kdm1bT357M and Kdm1bP281L). LSD1 and LSD2 were found to interact with circadian clock proteins in vitro. The LSD1 mutations were found to decrease the ability of LSD1 to bind to its primary cofactor CoREST and to CLOCK, BMAL1 and PER1 and PER2. Furthermore, chromatin immunoprecipitation studies were used to investigate LSD1 mutant binding of circadian promoters and demethylation of histone H3. Non-significant impairment of demethylase activity and binding suggest that the resulting phenotype is more subtle than in knockout cells. In vivo, adult LSD1 and LSD2 mutant animals were shown to display background strain-dependent circadian phenotypes. Kdm1aE440G/E440G animals displayed a deficit in circadian masking but a normal phase response to nocturnal light pulses and normal pupillary constriction. This suggests that LSD1 plays a role in phase resetting. Kdm1bT357M/T357M animals displayed an increased phase shift in response to 15-minute light pulses at CT22 indicating a phase resetting phenotype. Gene expression in mutant animal livers was assessed and only subtle changes in circadian gene expression were observed. In neurobehavioural phenotyping, Kdm1aE440G/E440G mutants were hyperresponsive to handling, showed impaired learning and memory, and displayed subtle discrepancies in anxiety and social dominance parameters. Kdm1bT357M/T357M animals displayed less neurobehavioural abnormalities, including an increase in time freezing in response to foot shock in fear conditioning. Histological examination revealed a hypogonadal phenotype in Kdm1aME440G/E440G animals which may be accounted for by disruption of the previousl established developmental roles of LSD1. Finally a screen of epigenetic modifier compounds revealed that small molecule demethylase inhibitors alter circadian period in fibroblasts and in the SCN itself. This investigation lends an insight into the roles of LSD1 and LSD2 in the circadian system and neurobehaviour and identifies future avenues of investigation that could clarify these roles further.